2013
DOI: 10.1002/ps.3672
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and insecticidal activities of novel pyrazole oxime ether derivatives with different substituted pyridyl rings

Abstract: Structure-activity relationships were also examined. Results suggested that the tert-butoxycarbonyl group, as well as the position between tert-butoxycarbonyl and the atom N of the pyridyl ring, were essential to obtaining the acarcidal activity of the title compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 19 publications
0
28
0
2
Order By: Relevance
“…activities [1][2][3]. Perimidines also can be used as dyes and have a wide application in industrial eld, and the famous product was reported as solvent black 3 [4].…”
Section: Discussionmentioning
confidence: 99%
“…activities [1][2][3]. Perimidines also can be used as dyes and have a wide application in industrial eld, and the famous product was reported as solvent black 3 [4].…”
Section: Discussionmentioning
confidence: 99%
“…Perimidines have drawn extensive examinations of many researchers recently [4][5][6]. There are several preparative methods for the synthesis of perimidine derivatives [7,8].…”
Section: Commentmentioning
confidence: 99%
“…Perimidines have long attracted the attention of researchers because they exhibit a diverse range of biological activities [4][5][6][7]. Perimidines can also be used as dyes and have a wide application in industrial field with solvent black 3 being a notable example 3 [8].…”
Section: Commentmentioning
confidence: 99%